2020
DOI: 10.1002/sia.6928
|View full text |Cite
|
Sign up to set email alerts
|

pH‐dependent lubrication mechanism of graphene oxide aqueous lubricants on the strip surface during cold rolling

Abstract: The tribological performance and lubrication mechanism of graphene oxide (GO) aqueous lubricants with different pH levels on the strip surfaces during cold rolling were investigated. And triethanolamine (TEA) was used to adjust the pH levels of GO lubricants. The morphology of GO and physical characterization of GO lubricants were carried out. Four‐ball tribological tests and cold rolling experiments were conducted to obtain the tribological behaviors of GO lubricants on the strip surfaces. To figure out the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…The GO solution at pH=10 did not show any lubricant properties. However, Meng's research [50] found that alkaline GO suspension (pH=9) adjusted by triethanolamine behaved better lubrication performance on the strip surfaces during cold rolling. The COF, wear scar diameter, and the minimum rolling thicknesses of the rolled strips in GO aqueous suspension (pH=9) decreased by 28.6%, 21.6%, and 10.84%, respectively, and the last nonseizure load decreased by 20%, versus GO aqueous suspension with pH of 2.8.…”
Section: Influence Of the Ph Environment Of Gomentioning
confidence: 97%
“…The GO solution at pH=10 did not show any lubricant properties. However, Meng's research [50] found that alkaline GO suspension (pH=9) adjusted by triethanolamine behaved better lubrication performance on the strip surfaces during cold rolling. The COF, wear scar diameter, and the minimum rolling thicknesses of the rolled strips in GO aqueous suspension (pH=9) decreased by 28.6%, 21.6%, and 10.84%, respectively, and the last nonseizure load decreased by 20%, versus GO aqueous suspension with pH of 2.8.…”
Section: Influence Of the Ph Environment Of Gomentioning
confidence: 97%
“…In the case of pH-dependent GO as water-based nanoadditives, two studies were reported by He et al [17] and Meng et al [76], which proposed two different preparation processes. A mechanical de-agglomeration method was used by He et al [17] to prepare GO suspension with 0.06 wt.% GO and 0.1 M NaOH in DW under high intensity ultrasonic agitation (400 W) for 10 min, resulting in good dispersion stability for a week.…”
Section: Carbon-based Materialsmentioning
confidence: 99%
“…The pH value was adjusted by NaOH and varied from 3.1 to 9.7, which had insignificant influence on agglomeration of GO sheets. In contrast, Meng et al [76] mixed triethanolamine (TEA) with 0.1 wt.% GO in DIW to adjust the pH value from acidic (pH 2.8) to alkaline (pH 9). They found that the lubricant with pH 9 was the most homogeneous with no precipitation for 50 days.…”
Section: Carbon-based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cold rolling was one of the most important metal forming processes to obtain the required size, mechanical properties, and surface finish 1,2 . But the friction and wear caused great losses in materials and energy, which remained a challenge to be addressed at present 3,4 .…”
Section: Introductionmentioning
confidence: 99%